Distribution of transposable elements in Drosophila species. - Biemont, C.; Cizeron, G. (Genetica, 1999)
We present a global analysis of the distribution of 43 transposable elements (TEs) in 228 species of the Drosophila genus from our data and data from the literature. Data on chromosome localization come from in situ hybridization and presence/absence of the elements from southern analyses. This analysis shows great differences between TE distributions, even among closely related species. Some TEs are distributed according to the phylogeny of their host species; others do not entirely follow the phylogeny, suggesting horizontal transfers. A higher number of insertion sites for most TEs in the genome of D. melanogaster is observed when compared with that in D. simulans. This suggests either intrinsic differences in genomic characteristics between the two species, or the influence of differing effective population sizes, although biases due to the use of TE probes coming mostly from D. melanogaster and to the way TEs are initially detected in species cannot be ruled out. Data on TEs more specific to the species under consideration are necessary for a better understanding of their distribution in organisms and populations.